Analisis Stabilitas dan Perbandingan Metode Perbaikan Longsor Ruas Jalan Barung-Barung Belantai KM. 45+400, Pesisir Selatan - Zelby, Rahayu; Hakam, Abdul; Andriani, Andriani (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
The Barung-Barung Belantai road section is located in Pesisir Selatan Regency, West Sumatra. The area is dominated by steep hillsides that are prone to landslides. The types of slope reinforcement used are Gabion, Cantilever Retaining Walls and Sheet Piles. This study aims to calculate the slope safety factor value using the slice method, analyze slope reinforcement against the safety factors of overturning, sliding, soil bearing capacity and calculate the cost and time of the work. Based on the calculation of slope stability, the slope safety factor (Fs) value is 0.8569, overturning is 0.971, and the soil bearing capacity value is 0.996. These values ​​indicate that the slope condition is classified as unstable because all safety factor values ​​(Fs) are below 1.25, which is the safe limit. Based on this analysis, this study recommends the use of a 4-meter high cantilever retaining wall as a repair solution. The calculation results show that this wall has a safety factor (Fs) against shear of 4.920, overturning of 2.003, and soil bearing capacity of 4.730, including the safe category and meeting technical criteria. It is concluded that the cantilever wall is more efficient than the gabion and sheet pile methods. The construction of the cantilever wall requires a budget of Rp. 522,259,000 with a working time of 14 weeks. As a comparison, the construction of the gabion structure costs Rp. 560,974,000 with a work duration of 11 weeks, while the sheet pile costs Rp. 629,578,000.- with a work time of 10 weeks.